Dopant activation mechanism of Bi wire-δ-doping into Si crystal, investigated with wavelength dispersive fluorescence x-ray absorption fine structure and density functional theory. (15th March 2017) - Murata, Koichi; Kirkham, Christopher; Shimomura, Masaru; Nitta, Kiyofumi; Uruga, Tomoya; Terada, Yasuko; Nittoh, Koh-ichi; Bowler, David R; Miki, Kazushi
Abstract: We successfully characterized the local structures of Bi atoms in a wire- δ -doped layer (1/8 ML) in a Si crystal, using wavelength dispersive fluorescence x-ray absorption fine structure at the beamline BL37XU, in SPring-8, with the help of density functional theory calculations. It was found that the burial of Bi nanolines on the Si(0 0 1) surface, via growth of Si capping layer at 400 °C by molecular beam epitaxy, reduced the Bi–Si bond length from 2.79 ± 0.01 A ˚ to 2.63 ± 0.02 Å. We infer that following epitaxial growth the Bi–Bi dimers of the nanoline are broken, and the Bi atoms are located at substitutional sites within the Si crystal, leading to the shorter Bi–Si bond lengths.